2003
DOI: 10.1258/135763303322596345
|View full text |Cite
|
Sign up to set email alerts
|

A national survey of telehealth activity in Australian hospitals

Abstract: We conducted a national survey of Australian hospitals to assess their use of telehealth. Information was sought from the 814 hospitals with 10 or more beds, excluding the small number that provided only day surgery and seven for which we could not identify a contact person. A total of 564 replies were received (a 69% response rate). Nationally, nearly half (49%) reported that they were engaged in some telehealth activity. However, there was a significant difference across jurisdictions. Hospitals in the publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Public hospitals were more likely to embrace the technique than private hospitals, and it was found that the more remote the location, the higher was the likelihood of telehealth use. 8…”
Section: Discussionmentioning
confidence: 99%
“…Public hospitals were more likely to embrace the technique than private hospitals, and it was found that the more remote the location, the higher was the likelihood of telehealth use. 8…”
Section: Discussionmentioning
confidence: 99%
“…Chief executives primarily hold a managerial role and may not have day-to-day involvement in running certain activities such as telemedicine. Future studies may benefit from including a broad definition of telemedicine such as that used by Wootton et al 2 when making initial contact with participants.…”
Section: Discussionmentioning
confidence: 99%
“…The method used was adapted from a survey of telehealth activity in Australia by Wootton et al 2 11 The final list comprised 189 hospitals. A letter was sent to the first named person (Chief Executive, General Manager, Administrator, Medical Director or Matron) at 187 of the 189 hospitals requesting their assistance with the project; there was prior knowledge about telemedicine in the remaining two hospitals.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, as early as 2003, nearly half of all hospitals in Australia used some sort of telemedicine technology, with private hospitals being more likely than public hospitals to use it (Wootton et al 2003). Today, the figures are likely much higher, and not just in Australia.…”
Section: Telemedicinementioning
confidence: 99%